Sinandong Local Wisdom Tanjungbalai Malay Oral Traditions: Literary Anthropology Approach - Sari, Syafriani Tio (L'Geneus : The Journal Language Generations of Intellectual Society, 2019)
The sinandong oral tradition has lost its support because people rarely use this tradition. The tradition of bersinandong is currently only used at night ceremonies which are initiated in Malay traditional marriage ceremonies and as entertainment in shells party ceremonies and swinging children. Therefore, researchers are interested in raising this hum as research material so that the public can get to know it better. The writing of this thesis was done to describe the local wisdom contained in the Tanjungbalai Malay oral tradition synandong. To achieve this goal, the researcher uses literary anthropology theory. The data analysis technique was carried out by descriptive analysis. Local wisdom contained in the Sinandong oral tradition of Tanjungbalai Malay, namely hard work, education, health,